OPTIMALISASI JUMLAH PRODUKSI ROTI ADIL BAKERY DI DESA MEUSEE KECAMATAN KUTA BLANG KABUPATEN BIREUEN - Safira, Izya (LPPM Universitas Malikussaleh - Indonesia, 2024)
The Adil Bakery bread agroindustry is one of the industries that produces bread with contemporary variants, namely; Tiramissu bread, blueberry bread, strawberry bread, chocolate bread and srikaya bread. In the implementation of production and marketing activities, this bread agroindustry does not always run smoothly, there are several obstacles that occur, such as erratic bread sales every day, such as bread not being sold out within a day. Therefore, Adil Bakery requires optimal production quantity planning to determine the number of products that will be produced for each type of bread variant in a day. This research was conducted to analyze the optimal combination of bread production quantities and to determine the maximum amount of profit obtained by the Adil Bakery agroindustry. The data analysis method used is quantitative with a linear programming model using the simplex method with the help of QM For Windows software. The results of the research show that in one production the optimal bread production combination for the Adil Bakery bread agroindustry to produce maximum profits is 460 pcs of tiramissu bread, 750 pcs of blueberry bread, 750 pcs of strawberry bread, 1,080 pcs of chocolate bread pcs and 750 pcs of srikaya bread. Meanwhile, the maximum profit that will be obtained by the Adil Bakery bread agroindustry in one production is IDR 6,541.12 per five variants. If production is under optimal conditions, the profit contribution that Adil Bakery will receive will increase by IDR 3,105,236 per five variants from the profit contribution under actual conditions. Keywords: Agroindustry, Bread, Optimization, Profit